Herding dan Pendidikan dalam Keputusan Masyarakat Menjadi Nasabah Bank Syariah Indonesia (Studi Empirik Pada Bank Syariah Indonesia di Kota Jambi) - Ahmad Syahrizal (EKSISBANK (Ekonomi Syariah dan Bisnis Perbankan), 2022)
Islamic banks as a solution for usury-free banking transactions are becoming increasingly attractive to the public, as evidenced by the increasing market share of Islamic banks. Some of the factors that influence it include herding and education. This study aims to see and measure the extent to which herding and education factors influence the public's decision to become a customer of a sharia bank. Data was obtained by distributing questionnaires to customers which were then processed quantitatively for multiple linear regression analysis. Based on the partial test, the herding variable has no effect on the decision to become a customer of Bank Syariah Indonesia, but on the contrary, the education variable has a positive and significant influence.